Nanoarchitectonics of CdS/ZnSnO3 heterostructures for Z-Scheme mediated directional transfer of photo-generated charges with enhanced photocatalytic performance. (22nd February 2022) - Wang, Yingxian; Yang, Chunming; Zhang, Yuanyuan; Guo, Li; Wang, Yu; Gao, Ge; Fu, Feng; Xu, Bin; Wang, Danjun
Abstract: The construction of heterostructure is an effective strategy to synergetically couple wide-band-gap with the narrow-band-gap semiconductor with a mediate optical property and charge transfer capability. Herein, the Z-Scheme CdS/ZnSnO3 (CdS/ZSO) heterostructures were constructed by anchoring CdS nanoparticles on the surface of double-shell hollow cubic ZnSnO3 via the hydrothermal method. The direct recombination of excited electrons in the conduction band (CB) of ZSO and holes in the valence band (VB) of CdS via d-p conjugation at the interface greatly accelerated the internal electric field (IEF). The transfer mode follows the Z-Scheme mechanism, where CdS/ZSO synergistically facilitates the efficient charges transfer from CdS to ZnSnO3 through the intimate interface. Here, ZnSnO3 and CdS serve as an oxidation photocatalyst (OP) and reduction photocatalyst (RP), respectively. Thus, it can promote synergistically the oxidation half-reaction and reduction half-reaction of H2 evolution. The density-functional theory (DFT) calculation further confirms the charges transfer from CdS to ZnSnO3 . The hydrogen evolution of 5% CdS/ZSO heterostructure reached 1167.3 μmol g −1, which was about 8 and 3 folds high compared to pristine ZSO (141.9 μmol g −1 ) and CdS (315.5 μmol g −1 ), during 3 h of reaction respectively. Furthermore, the CdS/ZSO heterostructures could suppress the photo corrosion of CdS, resulting in its high stability. This work is expected to enlighten the rational design of heterostructure for OP and RP to promote the hybrid heterostructures photocatalytic H2 evolution. Graphical abstract: Image 1 Highlights: CdS/ZnSnO3 heterostructures were fabricated via a hydrothermal process. CdS/ZSO heterostructures shows much higher HER activity than CdS and ZnSnO3 . The CdS/ZSO heterostructures can suppress the photo corrosion of CdS. The Z-Scheme electron transfer mechanism of CdS/ZSO heterostructures was proposed.